Alkaloid compound identification of Rhodomyrtus tomentosa stem as biology instructional material for senior high school X grade - Ningrum, Retno; Purwanti, Elly; Sukarsono, Sukarsono (University of Muhammadiyah Malang, 2016)
Rhodomyrtus tomentosais one of herbs which belongs to myrtaceaefamily. This plant possessesalkaloid which is efficacious as anti diarrhea, anti diabetes, anti microbial, and anti malaria, however some alkaloid compoundsare poisonous. Thus,it is necessity to identify the alkaloid compounds contained in the stem of Rhodomyrtus tomentosa which are known the use. Thisresearch aimed to identify the types of alkaloid compoundsin the Rhodomyrtus tomentosa stem and find out its usesas the biology teaching materials in form of LKS (Student Work Sheet). The research was descriptive explorative which was purposed to describe the types of alkaloid compoundsin the Rhodomyrtus tomentosa stem. LC-MS (Liquid Chromatograpgy-Mas Spectroscopy) was employed in this research to analyze the compounds. The research results showed that there were seven types of alkaloid compounds within the Rhodomyrtus tomentosa, namely: maritidine (BM 288 m/z), berberine (BM 336 m/z), ismine (BM 258 m/z), tazettine (BM 332 m/z), lycorine (BM 288 m/z), deoxytazettine (BM 216 m/z), and homolycorine (BM 316 m/z). The results of the research has been used as biology teaching materials in senior high school X grade,The Biodiversity of Indonesia.